Microplastics in the surface waters of the South China sea and the western Pacific Ocean: Different size classes reflecting various sources and transport. (July 2022) - Cui, Yaozong; Liu, Mengyang; Selvam, S.; Ding, Yongcheng; Wu, Qianqian; Pitchaimani, V. Stephen; Huang, Peng; Ke, Hongwei; Zheng, Haowen; Liu, Fengjiao; Luo, Bojun; Wang, Chunhui; et al.
Abstract: Microplastic transport in the marginal seas is a key process influencing their ultimate fate in the open oceans. In the present study, we collected seawater samples from the western Pacific Ocean (WP) and the South China Sea (SCS) to investigate the distribution, transport, and possible sources for microplastics. Generally, the range of microplastic levels were 187–1816, 146–1563, and 34.2–622 particles/m 3 (averaged in 797 ± 512, 744 ± 330, and 201 ± 134 particles/m 3 ) for the northern SCS, the western SCS, and the WP, respectively. Based on the size distribution, the highest value (390 ± 288 particles/m 3 ) was found for 100–200 μm, followed by 200–500 μm (131 ± 155 particles/m 3 ), and 500–1000 μm (29.7 ± 39.2 particles/m 3 ), with the lowest for 1–5 mm (13.6 ± 14.2 particles/m 3 ). Granule, yellow, and size <1000 μm were their most prevalent characteristics. The main polymer types of microplastics were polyester, rayon, and nylon. A negative correlation between microplastic proportion and particle size was observed in the SCS and the WP. Furthermore, the main sources of microplastics in the northern SCS probably came from the Pearl River. Surface currents and the vertical mixing processes might be two different mechanisms that affect microplastic transport from the WP and the SCS. Future comparison to measured particle size distributions data allows us to explain size-selective microplastic transport in the marine environment, and probably provide guidance on microplastic longevity. Graphical abstract: Image 1 Highlights: Microplastic concentration was of low level in the SCS and the WP. Size distribution showed a gradual increase with decreasing particle size. Microplastics in the seas were influenced by coastal dynamics, like river plumes. Microplastics in the open oceans were more influenced by ocean currents.